The traditional and the modern in constructing axiological foundations of youth’s life prospects (Tuva and other regions) - Noyanzina, Oksana E.; Maximova, Svetlana G.; Omelchenko, Daria A. (The New Research of Tuva, 2023)
The aim of the article is to study life prospects and value orientations of young people in the Republic of Tuva in comparison with those living in other regions of the Siberian Federal District. The issue is considered in the context of examination of spiritual security of population as an integral condition of public consciousness and functioning of social institutes that provide the satisfaction of cultural and spiritual needs of the society. The authors analyze the results of a sociological study (a survey based on a structured online questionnaire) conducted in 2022. It covered ten regions of the Siberian Federal District, including the Republic of Tuva. The sample size was 5,000 people (n = 500 in each region, the population aged 14 to 35 years). Life goals of the Tuvan youth follow a general pattern that is characteristic to all young people of the district: material security — education — career advancement — creation of family — professional success. The focal point was certainly providing the material foundations of life. The Tuvan youth’s value configuration was quite different not only in the number of factors but also in their content. The youth in Tuva put the factor of patriotism first. It consists in opinions about symbolic and real ‘enemies’ and love for the homeland and is associated with the significance of assimilating the spiritual heritage of their nation. We definitely consider this as a national peculiarity of the Republic. If the common value structure in the Siberian Federal District had evident semantic differences by spheres of their realization, then these values were complementary in the consciousness of the Tuvan youth. The obtained data has confirmed our assumptions about a specific intertwining of the traditional and the modern in the way of life among the young population in the Republic of Tuva.